Study of Different Granule Size MCM-41 Molecular Sieve as Carrier of Amoxicillin - Li, Jing-Mei; Yu, Hui; Li, Xiao-Dong; Zhai, Qing-Zhou; Tian, Jian (Asian Journal of Chemistry, 2011)
In the study, two different granule size MCM-41 molecular sieves were synthesized by hydrothermal synthesis method under the different synthetical parameter. During the drug release, it is found that the drug was rapidly released from the carrier during the first 3 h. After this, the release rate became comparative lentitude. After 36 h, the release effect of the amoxicillin- (small-MCM-41) sample (SA) was 99 % and amoxicillin-(big-MCM-41) sample (BA) is 98 %. Compared SA and BA samples, the BA sample was released more rapidly in the first 3 h. However, it became more slowly after 3 h.